2017
DOI: 10.5152/jarem.2017.1099
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Platelet-Rich Plasma Treatment in Chondromalacia Patellae

Abstract: ÖZKondromalazi patella, patella arkasındaki kıkırdağın yumuşaması ve ilerleyen süreçte ülserleşmesiyle devam edebilen, diz önü ağrısı ile karekterize bir hastalıktır. Tedavisinde klasik fizik tedavi ve rehabilitasyon yaklaşımları, ağrı kesici ilaçlar, hasta eğitimi gibi tedavi yaklaşımları yer almaktadır. Son yıllarda kıkırdak lezyonlarında doku rejenerasyonu amacıyla PRP (Platelet-Rich Plasma) tedavisi daha da artan bir sıklıkta kullanılmaya başlanmıştır. Bu olgu sunumunda PRP tedavisi ile başarılı sonuç alın… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…HA and PRP (as well as its derivatives), however, have been extensively investigated in the literature for the treatment of musculoskeletal conditions of the knee, especially in terms of degenerative joint diseases [16,17]. Numerous studies [18][19][20][21][22][23][24][25][26][27][28][29] have demonstrated satisfactory outcomes associated with the application of both PRP and HA, although sometimes PRP may or may not prove to be slightly superior to HA. The effects elicited by PRP include cell recruitment, proliferation, differentiation, neovascularization, cytokine secretion, and inflammatory modulation [30].…”
Section: Gradementioning
confidence: 99%
“…HA and PRP (as well as its derivatives), however, have been extensively investigated in the literature for the treatment of musculoskeletal conditions of the knee, especially in terms of degenerative joint diseases [16,17]. Numerous studies [18][19][20][21][22][23][24][25][26][27][28][29] have demonstrated satisfactory outcomes associated with the application of both PRP and HA, although sometimes PRP may or may not prove to be slightly superior to HA. The effects elicited by PRP include cell recruitment, proliferation, differentiation, neovascularization, cytokine secretion, and inflammatory modulation [30].…”
Section: Gradementioning
confidence: 99%
“…HA and PRP (as well as its derivatives), however, have been extensively investigated in the literature for the treatment of musculoskeletal conditions of the knee, especially in terms of degenerative joint diseases [14,15]. Numerous studies [16][17][18][19][20][21][22][23][24][25][26][27] have demonstrated satisfactory outcomes associated with the application of both PRP and HA, although sometimes PRP may or may not prove to be slightly superior to HA. The effects elicited by PRP include cell recruitment, proliferation, differentiation, neovascularization, cytokine secretion and inflammatory modulation [28].…”
Section: Introductionmentioning
confidence: 99%